The past and future of urban philosophy - Константин Лидин; Алексей Буйнов (Проект Байкал)
Today’s problems of urban development management are extremely complex and diverse. This implies an appeal to the most general laws of nature, society and man, that is, to the methods of philosophy. The article shows the connection between Plato’s views and the worldview of modernism, between the philosophical views of Zeno of Elea and postmodernism. Each of these approaches, when applied consistently and fully, leads to very controversial and ambiguous results. It is concluded that it is necessary to maintain a balance when searching for the philosophical basis of each architectural solution.